Dietary Patterns of Females with Cholecystolithiasis: A Comprehensive Study from Central Region of Saudi Arabia - Rasheed, Naila; Almeshal, Razan A.; Almohaimeed, Wasaif S.; Almeshal, Emtenan A.; Alofee, Alhanuf M.; Alonazi, Adeem S.; Alshebrumi, Amal A.; Alghaith, Nada K.; Alotaibi, Wafa; Almogbel, Ebtehal; Khan, Muhammad Ismail (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Cholecystolithiasis is a worldwide gastrointestinal disorder and dietary pattern is one of the major risk factors involved in formation of cholelithiasis. AIM: This study was undertaken to determine the dietary patterns of female patients with cholecystolithiasis in the central region of Saudi Arabia. METHODS: A total of 332 females respondents were included, among them 157 were cholecystolithiasis cases, whereas 175 were healthy female subjects. All respondents were from central region of Saudi Arabia. Data were collected from a self-administered questionnaire and dietary patterns of studied population samples were compared by Chi-square test using SPSS software. RESULTS: The data showed that the consumption of meat from beef, lamb or goat, butter, ghee, pizza, cereals, legumes, coffee, tea, kabsa rice, tomatoes, and eggs was found to be positively associated with the risk of cholelithiasis. Interestingly, the data also demonstrated that consumption of cakes, chocolates, cookies, ice cream, doughnuts, chicken, fish or other sea foods, French fries, and hot dogs showed no relation with the risk of cholelithiasis. CONCLUSIONS: This study provides a comprehensive description of the dietary patterns of females from central region of Saudi Arabia and their association with the risk of onset of cholelithiasis. Specifically, the majority of non-vegetarian food stuffs showed positive association with the risk of development of cholelithiasis. These findings strongly recommended that the Health Ministry of Saudi Arabia should initiate the specific intervention public health programs on the dietary pattern in relation with the risk of cholelithiasis.